2020
DOI: 10.1038/s41559-020-1179-5
|View full text |Cite
|
Sign up to set email alerts
|

The Y chromosome may contribute to sex-specific ageing in Drosophila

Abstract: Heterochromatin suppresses repetitive DNA, and a loss of heterochromatin has been observed in aged cells of several species, including humans and Drosophila. Males often contain substantially more heterochromatic DNA than females, due to the presence of a large, repeat-rich Y chromosome, and male flies generally have shorter average life spans than females. Here we show that repetitive DNA becomes de-repressed more rapidly in old male flies relative to females, and repeats on the Y chromosome are disproportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
129
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(146 citation statements)
references
References 65 publications
(82 reference statements)
15
129
1
1
Order By: Relevance
“…The toxicity index measures the excess of intact TEs on an SLC, which represents the potential for genome-wide sex-specific mutational load as well as sex-specific genome instability. On the short time scale of individuals, a high toxicity index could lead to larger physiological differences between the two sexes [13]. In the long term, e.g., between populations and species, the accumulation of TEs as measured by the refugium index can have effects on reproductive isolation through TE/repressor mismatches, similarly to the situation in Drosophila [17,52].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The toxicity index measures the excess of intact TEs on an SLC, which represents the potential for genome-wide sex-specific mutational load as well as sex-specific genome instability. On the short time scale of individuals, a high toxicity index could lead to larger physiological differences between the two sexes [13]. In the long term, e.g., between populations and species, the accumulation of TEs as measured by the refugium index can have effects on reproductive isolation through TE/repressor mismatches, similarly to the situation in Drosophila [17,52].…”
Section: Discussionmentioning
confidence: 99%
“…Since only a subset of TE copies are usually capable of (retro)transposition, we propose a "toxicity index" as a quantitative measure for the excess of intact TE copies in the heterogametic vs. homogametic sex through the presence of an SLC (formula 1.2). The term "toxicity" pays tribute to the recently proposed "toxic Y" hypothesis in Drosophila [13], which suggested that an excess of Y-specific active TEs can lead to male-biased transposition and genome instability, together likely detrimental to the genome and the organism. For birds, we calculated the toxicity index as the excess of fl-ERVs carried by diploid females compared to diploid males ( Table 1), suggesting that females with heteromorphic sex chromosomes carried between 28 to 83% more fl-ERVs than males, and that even the emu has 13% more fl-ERVs in females than males despite largely homomorphic sex chromosomes [31,32].…”
Section: Enrichment Of Ervs On the W Chromosomementioning
confidence: 99%
See 3 more Smart Citations